"Here everyone is the same" - a qualitative evaluation of participating in a Boccia (indoor bowling) group: innovative practice - Ovenden, Imogen; Dening, Tom; Beer, Charlotte (SAGE, 2016)
This qualitative study explored the impact of a Boccia (modified indoor bowls) group on the lives of people with dementia and their carers. Semi-structured interviews with people with dementia (N=6), carers (N=10) and the group organisers (N=6) analysed using thematic analysis revealed four main themes. ‘The struggle of being a carer’ was relieved by participating in the group and benefiting from the caring support and social aspects of “This group is a family”. “The unique nature of Boccia” helped it to provide physical and mental stimulation as well as being an inclusive and enjoyable group. These aspects contributed to many participants describing the group as a Dementia friendly environment where “Here everyone is the same:” treated as equals, without feeling hindered or defined by dementia. Boccia appears an exciting initiative but further research is needed to see if these findings can be replicated with other groups.